The Effect of Work Stress on Affective Commitment Mediated by Organizational Justice - Ryan Fajri; Muhammad Rasyid Abdillah; Ririn Handayani (SAINS ORGANISASI, 2022)
This study aims to see how the high work stress experienced by the personnel of the Satreskrim and Satnarkoba Polresta Pekanbaru affects their affective commitment if the perceived organizational justice is adequate. This type of research is explanatory research. The population is the personnel of the Narcotics Unit and the Criminal and Investigation Unit of the Pekanbaru City Police, totaling 95 people. Data analysis in this study used SEM-PLS. Based on the data processing, it was found that there was a significant effect of work stress on affective commitment through organizational justice. Therefore, organizational justice is stated to be able to mediate the effect of job stress on affective commitment. The limitation of this study is the lack of population size used